2012
DOI: 10.1161/atvbaha.112.248161
|View full text |Cite
|
Sign up to set email alerts
|

ABO Blood Group and von Willebrand Factor Levels Partially Explained the Incomplete Penetrance of Congenital Thrombophilia

Abstract: Objective— We aimed to study the association among ABO blood group, von Willebrand factor, factor VIII plasma levels, and the risk of venous thrombosis (VT) in a cohort of 1774 relatives from 500 families with inherited thrombophilia. Methods and Results— One hundred sixty-one of the 1774 relatives had a VT. Different risk groups were formed: no, low-(factor V Leiden or F2G20210A heterozygous carriers), and high-risk thrombophilia (antithrombin, protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
(43 reference statements)
1
21
0
Order By: Relevance
“…We thus evaluated the impact of weak and common SNPs on the risk of VT within these families. We have recently demonstrated the contribution of ABO blood group in this cohort [6]. In the present study, two SNPs located in the F11 gene and one in the FGG gene were also found to be associated with the risk of VT. F11 gene polymorphisms are associated with changes in FXI plasma levels.…”
Section: Discussionsupporting
confidence: 68%
“…We thus evaluated the impact of weak and common SNPs on the risk of VT within these families. We have recently demonstrated the contribution of ABO blood group in this cohort [6]. In the present study, two SNPs located in the F11 gene and one in the FGG gene were also found to be associated with the risk of VT. F11 gene polymorphisms are associated with changes in FXI plasma levels.…”
Section: Discussionsupporting
confidence: 68%
“…Cancer and non-O blood group have associated with increased risk of thrombosis (Wu et al, 2008;Cohen et al, 2012). Furthermore, recent studies have reported an association between ABO blood group and the risk of various epithelial cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that an ABO blood group could contribute to thrombosis risk through modifications of von Willebrand factor (VWF) and factor VIII (FVIII) levels in plasma (40,41). On the other hand, several studies have revealed that ABO blood groups remain significantly associated with elevated prothrombotic risk, even after adjustment for FVIII or VWF levels (41,42). Elevated plasma levels of FVIII and VWF are also established risk factors for DVT (43).…”
Section: Other Genetic Risk Factorsmentioning
confidence: 99%